The SYSTEMATIC LITERATURE REVIEW: HALAL SUPPLY CHAIN MANAGEMENT PRACTICES ON ENVIRONMENTAL SUSTAINABILITY IN THE FOOD INDUSTRY - Kuncorosidi Kuncorosidi (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2026)
The halal food industry involves the processing and handling of food in accordance with Islamic law, requiring the implementation of halal supply chain management (HSCM) to ensure integrity and food safety throughout the supply chain. Waste management and environmental considerations are increasingly important to minimize food waste and support sustainable economic, social, and environmental value creation. This study aims to examine the relationship between halal supply chain management practices and environmental sustainability, as well as the suitability of HSCM in supporting sustainability, using a systematic literature review (SLR) approach. The findings indicate that research integrating HSCM and environmental sustainability remains limited. Stakeholder collaboration and Corporate Social Responsibility (CSR) practices are identified as key enablers of sustainability in the halal food industry. Supply-related risks emerge as the most significant risk category, requiring coordinated efforts from governments, suppliers, companies, and distributors, particularly in infrastructure, technology, and human resources. Notably, only 26% of the reviewed studies explicitly address environmental sustainability, highlighting substantial opportunities for future research.